2019
DOI: 10.1242/jeb.205112
|View full text |Cite
|
Sign up to set email alerts
|

Strain transformation: Enhancement of invertebrate memory in a new rearing environment

Abstract: Memory formation is influenced by a variety of factors, including the environmental conditions in which an organism is reared. Here, we studied the memory-forming ability of the lab-bred B-strain of Lymnaea stagnalis following a change in their rearing environment from Brock University to the University of Calgary. We have previously demonstrated that this move enhances memory-forming ability and here we studied the magnitude of this phenotypic change. Once reared to adulthood at the University of Calgary, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Interestingly, this transformation in the S-strain snails, of an ability typically only seen in freshly collected snails, by a cold spell for a 4 week period serves to remind us that this inbred laboratoryreared strain possesses great plasticity to alter its behaviour in light of changing environmental conditions. This has previously been demonstrated in the S-strain, as there was a metamorphosis from an average cognitive phenotype to a below-average cognitive phenotype when the studied snails had been conceived and reared in a different environment (Rothwell et al, 2018;Rothwell and Lukowiak, 2019). This metamorphosis of cognitive phenotype has persisted for many years, but what drove that transformation is still unknown.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Interestingly, this transformation in the S-strain snails, of an ability typically only seen in freshly collected snails, by a cold spell for a 4 week period serves to remind us that this inbred laboratoryreared strain possesses great plasticity to alter its behaviour in light of changing environmental conditions. This has previously been demonstrated in the S-strain, as there was a metamorphosis from an average cognitive phenotype to a below-average cognitive phenotype when the studied snails had been conceived and reared in a different environment (Rothwell et al, 2018;Rothwell and Lukowiak, 2019). This metamorphosis of cognitive phenotype has persisted for many years, but what drove that transformation is still unknown.…”
Section: Discussionmentioning
confidence: 56%
“…We should have expected strain-specific differences in similar behaviours based on our own published data (e.g. Dodd et al, 2018;Rothwell et al, 2018;Rothwell and Lukowiak, 2019). In the Dodd et al (2018) study, Lymnaea of one strain were able to recognize differences in another strain, even if the other strain was initially derived from the same founder colony.…”
Section: Discussionmentioning
confidence: 94%
“…The two strains of wild, freshly collected, smart snails exhibited configural learning in a similar manner to the laboratory-reared W-strain. Both the White Sand Lake and Stony Lake snails have been classified as smart snails (Hughes et al, 2017;Shymansky et al, 2017;Dodd et al, 2018;Rothwell and Lukowiak, 2019). Previously, Hughes et al, (2017) found that smart snails respond to combinations of stressors differently from 'average' freshly collected wild snails (the TC2 strain) or laboratory-bred W-strain snails.…”
Section: Resultsmentioning
confidence: 99%
“…strains) in their cognitive abilities. Thus, unique Lymnaea strains can be classified as exhibiting the following cognitive phenotypes: 'smart', 'average' and 'below-average', based on their ability to form long-term memory (LTM) following operant conditioning of aerial respiratory behaviour (Lukowiak et al, 1996;Orr et al, 2009;Sunada et al, 2017;Totani et al, 2019;Rothwell and Lukowiak, 2019). A smart cognitive phenotype strain, such as the TC1 or WSL strain, forms LTM with a single 0.5 h training session (Orr et al, 2009;Hughes et al, 2017), whereas in an average cognitive phenotype strain, such as the TC2 or W-strain, LTM requires two 0.5 h sessions (Dodd et al, 2018).…”
Section: Introductionmentioning
confidence: 99%